Crime detection - Oxlade, Chris (Crystal Lake, IL : Rigby Interactive Library, 1997)
Uses familiar examples to explain the science of crime detection, covering such aspects as fingerprints, clues in the human body, chemical evidence, and computers.
Includes index.
9 - 10 years
81506
Keywords: Criminal investigation; Forensic sciences